Parents’ spatial talk to boys and girls in museum settings: variations by science topic and exhibit scale - Umansky, Vera M.; Callanan, Maureen A. (Frontiers in Education, 2024)
Introduction: Children are exposed to STEM ideas, including spatial and other mathematical concepts, in a variety of everyday contexts through interactions with their parents. There may be variations in the spatial language that boys and girls hear from their parents within different informal contexts. The present study investigated variations in the frequency and type of parental spatial talk that occurred in museum settings that varied by topic (physical science vs life science) and exhibit scale (small-scale activity vs large-scale activity). Method: The sample consisted of 194 families with children between the ages of 3 to 6 who visited museums in Northern California. Of the total sample, 50 families visited a large-scale physical science exhibit, 44 families visited a large-scale life science exhibit, 50 families visited a small-scale physical science exhibit, and 50 families visited a small-scale life science exhibit. Parent-child conversations that occurred during the duration of the museum visit were coded for parents' spatial language. Results and Discussion: Analyses revealed that parents in the large-scale life science exhibit used more spatial language than parents in the other exhibits. Additionally, parents used more "where" spatial language (spatial language that describes location and directionality) than "what" spatial language (spatial language that describes the look of something) across the exhibit contexts, but especially in the large-scale exhibits. Finally, boys heard more "where" spatial language than girls across exhibit contexts, whereas there was no difference by gender for "what" spatial language exposure. Variations in the kinds of spatial language that parents use in different environments should be taken into account in developmental models of children's spatial understanding. Future research is needed to more systematically explore how parents' spatial language varies across children's gender, exhibit topic, and exhibit scale.